EXTH-68. DUAL METABOLIC REPROGRAMMING BY ONC201/TIC10 AND 2-DEOXYGLUCOSE HAS A STRONG ANTIPROLIFERATIVE EFFECT ON MEDULLOBLASTOMA CELLS. (12th November 2021) - Dwucet, Annika; Cao, Qiyu; Pruss, Maximilian; Westhoff, Mike-Andrew; Wirtz, Christian Rainer; Siegelin, Markus D; Karpel-Massler, Georg
Abstract: BACKGROUND: Medulloblastoma represents one of the most common brain tumors in children. While the understanding of the molecular characteristics of this disease has very much advanced, more efficient and less toxic therapeutics are still in high demand. In this study we examined whether the imipridone ONC201/TIC10 affects the metabolic and proliferative activity of medulloblastoma cells alone and in combination with 2-Deoxyglucose in vitro. METHODS: Extracellular flux (agilent seahorse) and Western blot analyses were performed to assess effects on tumor cell metabolism and the expression of proteins of the respiratory chain in established medulloblastoma cells. MTT assays and spheroid assays were performed to examine anti-proliferative effects in a 2-D and 3-D setting. RESULTS: Treatment with ONC201/TIC10 has a strong inihibitory effect on the cellular viability of different medulloblastoma cells independent of c-Myc expression. While ONC201/TIC10 decreases the oxidative consumption rates in D458 (c-Myc high) and DAOY (c-Myc low) cells, extracellular acidification rates experienced an increase in D458 and a decrease in DAOY cells. Treatment with ONC201/TIC10 in combination with the glycolysis inhibitor 2-Deoxyglucose synergistically inhibited the cellular viability of medulloblastoma cells and impaired the growth of spheroids. CONCLUSION: Overall, ONC201/TIC10 profoundly inhibits the proliferative activity of medulloblastoma cells in a c-Myc-independent manner. Additional treatment with the glycolysis inhibitor 2-Deoxyglucose synergistically enhances the anti-medulloblastoma activity of ONC201/TIC10. This promising approach warrants further investigations.